ANALYSIS OF KNOWLEDGE ABOUT FLOUR FOR READINESS OF PASTRY PRACTICE OF STUDENTS STUDY PROGRAM DIII HOSPITALITY HARAPAN BERSAMA POLYTECHNIC IN TEGAL - Anggraeni, Puput Dewi; Sabrina, Tantri Adithia (UI Scholars Hub, 2020)
Students of DIII Hospitality Harapan Bersama Polytechnic inTegal are equipped with a number of productive courses, one of which is the Pastry course, where this course learns from the preparation, manufacturing, serving to storage of bread and cake with standard recipe specifications and company practices. But the knowledge of some students is still very low in the material